2014
DOI: 10.1177/0270467614538002
|View full text |Cite
|
Sign up to set email alerts
|

Facebook Influence Among Incoming College Freshmen

Abstract: Alcohol displays on Facebook are ever-present and can be socially desirable for college students. As problematic drinking is a concern for college students, this research sought to understand how different types of information on a Facebook page influence likelihood to drink. Telephone interviews were conducted with 338 incoming college freshmen from two large national universities. Data were obtained from a vignette prompt which presented a scenario in which a senior college student’s Facebook profile display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…When forming impressions of others in an online environment, social information processing theory argues that the perceiver utilizes all of the information available but that cues which are particularly prominent, or ''sticky cues'', grab the attention of the observer and play a larger role in influencing their judgment and impressions of the individual (Van der Heide & Schumaker, 2013). For example, sticky cues about alcohol use on Facebook have been studied with regard to their influence on viewers' intention to drink, with wall posts (comments) being the stickiest, followed by pictures (D'Angleo, Zhang, Eickhoff, & Mereno, 2014). We would argue that the prominence of these sticky cues make them a likely source of information to be used in cyberbullying and, depending on the personality and motives of the observer, this information could be used to shame, humiliate, or threaten others on Facebook (Rafferty & Vander Ven, 2014).…”
Section: Impact Of Risky Sns Practices On Cyberbullying Victimizationmentioning
confidence: 99%
“…When forming impressions of others in an online environment, social information processing theory argues that the perceiver utilizes all of the information available but that cues which are particularly prominent, or ''sticky cues'', grab the attention of the observer and play a larger role in influencing their judgment and impressions of the individual (Van der Heide & Schumaker, 2013). For example, sticky cues about alcohol use on Facebook have been studied with regard to their influence on viewers' intention to drink, with wall posts (comments) being the stickiest, followed by pictures (D'Angleo, Zhang, Eickhoff, & Mereno, 2014). We would argue that the prominence of these sticky cues make them a likely source of information to be used in cyberbullying and, depending on the personality and motives of the observer, this information could be used to shame, humiliate, or threaten others on Facebook (Rafferty & Vander Ven, 2014).…”
Section: Impact Of Risky Sns Practices On Cyberbullying Victimizationmentioning
confidence: 99%
“…Problematic social media use may negatively affect psychosocial functioning (Tsitsika et al, 2014) and may increase risk of problem drinking, particularly when content is alcohol related (D'Angelo et al, 2014;Geusens & Beullens, 2017;Glassman, 2012;Moreno et al, 2012;Ridout et al, 2012;Thompson & Romo, 2016;Westgate et al, 2014). For example, Marczinski et al (2016) found that college students' alcohol-related Facebook activity (e.g., written postings or photos/images depicting alcohol) predicted hazardous drinking.…”
mentioning
confidence: 99%
“…Picture information is not only easily accessible to form a quick initial impression, but also carries a great impression formation weight. A visual primacy effect is found before, emphasizing the importance of profile pictures over profile texts when forming impressions about Facebook profile owners (D'Angelo et al, 2014;Van der Heide et al, 2012). Pictures carry more weight in the final assessment (e.g., Fiore et al, 2008) and are also more likely to attract initial attention (Scott & Hand, 2016;Seidman & Miller, 2013).…”
Section: Processing and Assessing Profile Cuesmentioning
confidence: 75%